The Role of Ultrasonography in The Diagnosis of Oral and Maxillofacial Disease - Ni Putu Mira Sumarta1 , David Buntoro Kamdjaja2 , Roberto Manahan Yantie Simandjuntak3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objective: Ultrasonography, as a diagnostic tool, constitutes a non-invasive, cost-effective, readily-availableand repeatable imaging technique. Ultrasonography has been used as a means of diagnosing various medicalconditions for many years. However, in the field of maxillofacial surgery it represents a relatively new aidin the diagnosis of various diseases affecting the oral and maxillofacial regions. These include: infection,soft-tissue related diseases and vascular anomalies which can be detected using Doppler ultrasonography.This article presents four cases, in which ultrasonography was employed to confirm diagnoses and act as aguide to treatment. Methods: Four cases of soft tissue swelling and enlargement were diagnosed with theaid of ultrasonography, namely: a submasseteric abscess, a nasolabial cyst, a dermoid cyst and a left buccalspace abscess caused by a foreign body (i.e. a fish bone). Result: In the case of a submasseteric abscess,ultrasonography was used in confirming the diagnosis and therapy, while determining the maximal point ofthe abscess. In the cases of both cysts, ultrasonography highlighted well-defined cystic lesions with internalecho showing fluid accumulation, while in the buccal space abscess, an ultrasonogram confirmed the exactlocation of the fish bone. Conclusion: Ultrasonography is a quick, widely-available, relatively inexpensive,painless procedure which can be repeated as often as necessary without risk to the patient. Thus, ultrasonographyis a valuable diagnostic aid to the oral and maxillofacial surgeon in achieving early and accurate diagnosis.